Mapping Galilee in Josephus, Luke, and John: critical geography and the construction of an ancient space - Vonder Bruegge, John M. (Ancient Judaism and early Christianity, 2016)
Preliminary Material /John M. Vonder Bruegge -- 1 Galilee and Critical Geography: The Lay of the Land /John M. Vonder Bruegge -- 2 Josephus’ Galilee /John M. Vonder Bruegge -- 3 Luke’s Galilee /John M. Vonder Bruegge -- 4 John’s Galilee /John M. Vonder Bruegge -- 5 Galilee and Critical Geography: A New “Spatial Turn” /John M. Vonder Bruegge -- Bibliography /John M. Vonder Bruegge -- Index of Modern Authors /John M. Vonder Bruegge -- Index of Ancient Sources /John M. Vonder Bruegge -- Index of Geographical Features and Locales /John M. Vonder Bruegge -- Index of Subjects /John M. Vonder Bruegge.